Early biochemical predictors of sepsis in patients with burn injury: current status and future perspectives. Issue 3 (July 2020) - Erenler, Ali K.; Baydin, Ahmet; Ay, Mehmet O.; Doğan, Güvenç; Yasti, Ahmet Ç.
Abstract : N/A: Sepsis is the leading cause of morbidity and mortality in patients with burn injury and emerges as a clinical challenge for both emergency specialists and critical care staff. Since early diagnosis and appropriate treatment are known to be the milestones of sepsis management, use of biomarkers in diagnosis is highly recommended in the initial stage of sepsis. Although currently used Procalcitonin, as a traditional marker, may accurately indicate the presence of a systemic inflammation in burn patients, there is a need for more accurate markers of sepsis in burn patients. For now, use of a combination of markers may be suggested for a more accurate diagnosis. In the near future, gene therapy may make not only early prediction, but also appropriate treatment of sepsis in burn patients possible. In this article, we aimed to clarify roles of current biomarkers in early diagnosis of sepsis in burn patients and make future reflections in this growing field.